A Contrastive Analysis between English Idioms and Their Indonesian Equivalents in the Book Tintin in America by Herge (1932) - Nugroho, Muhammad Irfan; Jumanto, Jumanto (RIRAI Publisher, 2024)
This study focuses on employing a descriptive and qualitative research approach. The objective of this research is to discern similarities, differences, predictions of translating problems based on similarities and differences between English Idioms and their Indonesian equivalents. The analysis focuses on the book Tintin in America by Herge (1932). The results indicated the presence of 55 English idioms which consisted of 22 verbal idioms, 12 informal idioms, 5 idioms containing special keywords, 4 idioms related to specific themes, and 12 idiomatic pairs. Regarding the similarities and differences, within the Verbal Idiom category, researchers observed that there was 0 similarity between the 55 English Idioms and their Indonesian counterparts, and there were 55 differences between the 55 English Idioms and their Indonesian counterparts. Based on the differences, Indonesian learners may face problems when translating informal idioms, idioms containing special keywords, idioms related to specific themes, and idiomatic pairs. Within informal idioms, the Indonesian learners may make a mistake by translating, for example, It looks pretty phoney to me into *Bagi saya itu terlihat sangat palsu, instead of the better one Mencurigakan sekali. This is because the English expression is idiomatic, while its Indonesian equivalent is non-idiomatic. A word-by-word or literal translation is probably made due to the difference. The case may also happen when the Indonesian learners are translating idioms containing special keywords, idioms related to specific themes, and idiomatic pairs, for example: the English expression Good gracious! into the Indonesian equivalent *Baik hati, instead of the better one Astaga!; the English expression Glad to be back on my feet again into the Indonesian equivalent *Senang bisa kembali dengan kaki saya lagi, instead or the better one Senang sudah bisa jalan lagi; and the English expression The whole bunch of cut-throats into the Indonesian equivalent *Sejumlah pemotong tenggorokan, instead of the better one Semua bandit yang ada disini